Tabuh Pat Lelambatan Pari Anom in the Karawitan Composition and Its Psychological Influence on Gamelan Players - Yoga, I Nyoman Wiradarma; Yudarta, I Gede; Mawan, I Gede (Institut Seni Indonesia Bali, 2024)
This study aims to explore Tabuh Pat Lelambatan Pari Anom within the framework of musical composition and the psychological influence on gamelan musicians. Tabuh Lelambatan is a form of musical system that exists in the Gong Gede gamelan in its classical form. As a system, the tabuh of the lelambatan accommodates various types of tabuh, one of which is the Tabuh Pat Lelambatan. In this research, the Tabuh Pat Lelambatan Pari Anom was used as the research subject because this tabuh has fluctuating dynamics in its compositional presentation which results in an influence on the psychology of gamelan players when playing it. This was the background for this research which was then carried out using qualitative methods. The transcription of Tabuh Pat Lelambatan Pari Anom notation was used as a scalpel in detailing the data and interviews were also used as a data collection technique. This tabuh which can reach the realm of psychology is an opportunity to become an additional point in achieving the aim of this research, namely as academic information related to the psychological role of the performance of Tabuh Pat Lelambatan, in this case, Tabuh Pat Lelambatan Pari Anom.